Penyusunan Modul dan Pelatihan Manajemen Pembelajaran Online Berbasis Kecakapan Abad 21 Pada Guru SMP dan SMA Yayasan Pendidikan Islam Terpadu Alkautsar Duri, Kabupaten Bengkalis - Daeng Ayub; Sumardi; M. Jaya Adi Putra (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
Education In the 21st century, the world is changing very rapidly. This change concerns all lines of life, namely the fields of economy, transportation, technology, communication, information, and others. These changes are necessary to develop 21st century skills. These 21st century skills include critical thinking and problem solving, creativity and innovation, communication, and collaboration. The development of 21st century skills can be done in all disciplines. The main purpose of this activity is to be able to develop online learning modules so that teachers can improve the quality of 21st century skills-based learning based on learning management in SMP and SMA Alkautsar Duri Integrated Islamic Education Foundation, by making modules and conducting training. The time for the implementation is 4 days with 40 teachers participating. The results obtained that the level of understanding achieved in online learning modules, material achievement, namely about 21st century skills-based learning, the achievement of the types of online applications used, as well as the absorption of online applications based on modules in the context of 21st century skills, can all be categorized as high or good. . Foundations and schools need to continue to improve and develop 21st century skills-based online learning based on existing modules.